PENGARUH PENAMBAHAN FLY ASH DAN KONDISI ADUKAN TANAH LIAT TERHADAP KUAT TEKAN BATA MERAH - Astriani, Nelly; Elhusna, Elhusna; Wahyuni, Ade Sri (Universitas Bengkulu, 2017)
This article describes the research result of the effect of adding fly ash and water concentration of clay on red bricks’ compressive strength. Fisis characteristic and bricks’ compressive strength is according to SNI 15-2094-2000. Variation of fly ash that were used were 5%, 10%, 15%, 20%, 25%, and 30% from the weight of clay. Adding water concentration was based on three criterions of mortar clay condition, namely hard, normal, and soft. Hardmortar clayis a condition of the clay mixture which used less water than the normal mixture. Normal mixture is a condition ofthe clay mixture which usedwater based on usual concentration in brick factory. Soft mixture is a condition ofthe clay mixture that used much water than normal mixture. In this research, there are 8 sample for normal bricks and there are 144 sample for variation bricks. The optimum value of compressive strength for hard and normal mixture of variation bricks were obtained in 10% of fly ash variation which increased 33,59%, and 2,82% from normal bricks. Compressive strength for soft mixture of bricks was obtained in 5% of fly ash variation which increased 28,25% from normal bricks.